Water quality assessment - Boelee, Eline; Senzanje, Aidan; Munamati, M.; Parron, L.; Rodrigues, L.; Laamrani, Hammou; Cecchi, P. (2009)
One of the health risks of small reservoirs is the potential for increased transmission of water-related diseases, in particular, parasitic infections dependent on water-based “vectors”. The design, use, and management of reservoirs all influence their suitability as breeding grounds for disease vectors. This tool describes the use of selected methods to help stakeholders understand the ecological preferences of vector organisms in relation to small reservoirs. This is an important step in identifying management options for environmental disease control.